Hubungan Psychological Well-Being dengan Burnout pada Guru SMA Adabiah 2 Padang - Indah Gamma Edyani; Krisnova Nastasia (TSAQOFAH, 2026)
High work stress and emotional exhaustion among teachers can affect physical, emotional, and mental conditions, as well as reduce performance in carrying out professional duties. In this context, psychological well-being is an important aspect that has the potential to be associated with burnout levels because it includes self-acceptance, positive relationships with others, and environmental mastery. This study aims to determine the relationship between psychological well-being and burnout among teachers at SMA Adabiah 2 Padang. This study used a quantitative approach with a correlational design. The research participants consisted of 61 teachers at SMA Adabiah 2 Padang who were selected through total sampling. Data were collected using a psychological well-being scale consisting of 48 items with a reliability of α = 0.918 and a burnout scale consisting of 24 items with a reliability of α = 0.880, then analyzed using the Pearson correlation test. The results of the study show a significant negative relationship between psychological well-being and burnout (r = -0.613; p < 0.01), meaning that the higher the psychological well-being, the lower the level of burnout experienced by teachers. Psychological well-being made an effective contribution of 37.57% to burnout. The conclusion of the study affirms that psychological well-being has an important relationship with reduced burnout among teachers. The implications of this study indicate the need to develop programs to improve psychological well-being in the school environment to help teachers manage work pressure, maintain psychological well-being, and sustain professional performance more effectively.